Frederick County, Virginia, marriages, 1771-1825 - Davis, Eliza Timberlake (Baltimore, Genealogical Pub. Co., 1973)
Frederick County, with Augusta County, at one time embraced all of West Virginia,Kentucky, Ohio, Indiana, Illinois, Michigan, and Wisconsin. The 4,000 marriage records compiled in this volume (mostly bonds and ministers' returns) should be of particular interest to researchers whose forebears crossed the Blue Ridge Mountains.
Reprint of the 1941 ed.
74739
Keywords: Marriage records -- Virginia -- Frederick County; Registers of births, etc. -- Virginia -- Frederick County; Frederick County (Va.) -- Genealogy